2001
DOI: 10.1074/jbc.m103650200
|View full text |Cite
|
Sign up to set email alerts
|

Halotolerant Cyanobacterium Aphanothece halophyticaContains an Na+/H+ Antiporter, Homologous to Eukaryotic Ones, with Novel Ion Specificity Affected by C-terminal Tail

Abstract: Recently, a cyanobacterium Synechocystis sp. PCC 6803 has been shown to contain an Na ؉ /H ؉ antiporter gene homologous to plants (SOS1 and AtNHX1 from Arabidopsis) and mammalians (NHEs from human) but not to Escherichia coli (nhaA and nhaB). Here, we examined whether a halotolerant cyanobacterium Aphanothece halophytica has homologous genes. It turned out that A. halophytica contains an Na ؉ /H ؉ antiporter homologous to plants, mammalians, and some bacteria (nhaP from Pseudomonas and synnhaP from Synechocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 31 publications
(44 reference statements)
4
77
0
Order By: Relevance
“…However, the expression of a Na ϩ ͞H ϩ antiporter from Vibrio alginolytica NhaAv resulted in a Na ϩ -sensitive transformant (16). Recently, we isolated a eukaryotic Na ϩ ͞H ϩ antiporter gene (apnhaP) from a halotolerant cyanobacterium Aphanothece halophytica and showed that ApNhaP exhibits high Na ϩ ͞H ϩ exchange activity over a wide range of pH with novel ion specificity (17). Therefore, it was interesting to examine the effects of expression of ApNhaP and genes for the synthesis of betaine, catalase, and a chaperone (DnaK) and their combinations.…”
Section: Aphanothece Halophytica ͉ Genetic Engineeringmentioning
confidence: 99%
“…However, the expression of a Na ϩ ͞H ϩ antiporter from Vibrio alginolytica NhaAv resulted in a Na ϩ -sensitive transformant (16). Recently, we isolated a eukaryotic Na ϩ ͞H ϩ antiporter gene (apnhaP) from a halotolerant cyanobacterium Aphanothece halophytica and showed that ApNhaP exhibits high Na ϩ ͞H ϩ exchange activity over a wide range of pH with novel ion specificity (17). Therefore, it was interesting to examine the effects of expression of ApNhaP and genes for the synthesis of betaine, catalase, and a chaperone (DnaK) and their combinations.…”
Section: Aphanothece Halophytica ͉ Genetic Engineeringmentioning
confidence: 99%
“…It has been shown that the activity of H ϩ -coupled antiporters can be affected by modifications at the C or N terminus (29)(30)(31)(32). To test whether the C or N terminus of AtNHX1 plays a role in regulating antiporter activity, we measured the H ϩ -coupled cation transport activity in vacuoles containing the full length AtNHX1 and the N or C terminus truncated forms of AtNHX1 (Fig.…”
Section: Hamentioning
confidence: 99%
“…A. halophytica DnaK has been shown to contain the longer C-terminal segment than other DnaK/Hsp70 family members (21) and exhibit extremely high protein folding activity at high salinity (22). It was also shown that A. halophytica Na ϩ /H ϩ antiporter has novel ion specificity (23) and could confer the tolerance for salt stress of fresh water cyanobacterium capable of growing in sea water (24). Here, we show that in contrast to other oxygenevolving photosynthetic organisms, A. halophytica synthesizes betaine from glycine by a three-step methylation.…”
mentioning
confidence: 93%
“…Homology searches were made using the BLAST program as previously described (23). Two methyltransferase genes, ORF1 and ORF2, homologous to EcGSMT and EcSDMT were found and amplified by the PCR reactions using the genomic DNA of A. halophytica as a template.…”
Section: Methodsmentioning
confidence: 99%